Pengurangan Hambatan Aliran pada Celah Silinder Koaksial Akibat Slip - Yanuar .; Gunawan .; M. Baqi (Institute of Research and Community Outreach, Petra Christian University, 2010)
Slip effect which occurs at the wall due to the layer of water repellent wall can reduce the pressure drop. The highly water repellent wall coating on the inside coaxial viscometer slip will be occur. The aim of experiment is proving drag reducing of the torque on the cylinder and the coefficient of velocity slip due to the water repellent coating on the wall. Teflon and wax materials are used to coat the surface of the wall. Contact angle of water droplets with a Teflon-coated walls and waxed each of about 110º and 130º into flat surface. The ratio of the radius of inner cylinder and outer cylinder are 0.932 and 0.676. Glycerin solution with concentration 60%, 70% and 80% wt used the test fluid. The maximum drag reduction occurred is 12% for 80% wt glycerin solution at the 0.932 ratio of the radius. The calculation analysis of the moment coefficient fit with experimental data.